“Cuatro dosis de materia orgánica (gallinaza de postura), en el cultivo de cebolla china (var. Roja chiclayana), en la provincia de Lamas” - Rojas Montoya, Willy (2015)
This research aimed to evaluate and determine the effect of the application of four doses of organic matter in the development, growth and yield of green onion (Allium fistosum) Var. Red Chiclayana under agroecological in the province of Lamas and perform economic analysis of the treatments under study conditions. The research was conducted on the grounds of the Fundo "The Pacific" owned by Mr. Jorge Luis Pelaez Rivera, politically located in the district and province of Lamas, San Martin department. The statistical design of randomized complete block design {RCBD) with tour blocks and five treatments, with a total of 20 experimental units was used. The information gathered in the field was processed using SPSS 19 statistical software, which uses the P-value as meaningful comparison to the confidence levels of 0.05 and 0.01 differences in the analysis of variance (ANOVA) and multiple range test of Ouncan P s 0.05. The variables evaluated were: diameter of the neck of the plant, bulb diameter (cm), plant length (cm), the total plant weight (g), yield in kg ha-1 , and economic analysis. Sowing was done directly in final field using a bulb hole green onion variety Red Chiclayana at a depth of 1 cm, A gap of 0.20 m between row and 0.08 m between plants. Harvest, fur performed when the variety market reached maturity, and performed manually. The choice was made when market reached maturity, and performed manually. The results indicate that treated with doses of 30 t ha-1 posture manure treatment plants was more determining which resulted in obtaining increased performance with 62.587 kg ha-1 and the one produced higher benefit I cost with a value of 1.68, generating higher net profit, with a value of 13704.78 New Soles, respectively. Keywords: Doses, four, matter, organic, green, onion, evaluate, determine, Red, Chiclayana.